¿ Existe el cáncer localizado de próstata? - Lobel Mandel, Bernard; Guille Sendrales, Francois; Patard Roulier, Jean-Jacques; Zegarra Montes, Luis (Revista Médica Herediana, 2013)
The natural history of prostate cancer is not well defined and this further complicates the therapeutic options for its treatment. Since 1980, radical prostatectomy was considered the first option in attempting to cure this type of cancer which represents a 25% of the cases of cancer in men, affecting 1/8 of the male population before age 75 and that reveals itself as the more frequent male cancer after age 50. Due to its effectiveness, radical prostatectomy should be performed when cancer is limited to the gland, not having surpassed the prostatic gland. The acquired experience shows that 20-40% of anatomical pieces extracted presented capsular invasion or positive margins, and that approximately 30-60% of the operated patients witness the progress of their disease within 5 years, despite surgery. This thought is possible due to the acquired experience with numerous patients that have been treated with radical prostatectomy. All the recent work done confirms that only cancer localized to the prostatic gland is susceptible of being cured by surgery and that only low risk cancers have a real possibility of being limited to the gland. In this group of patients with localized cancer, many are not of clinical importance. An important number of patients that have neoplasic cells in their prostate will die from other causes, without having necessarily suffered from the prostate. This paper highlights the limits of surgery and the actual lack of criteria to define a localized lesion within the gland and its aggressiveness, as well as the lack of alternative effective treatments in the case of an extra prostatic lesion. Finally, it is very important to try to make an early diagnosis of prostatic cancer, nevertheless, from the moment in which the diagnosis of cancer is given to the patient, the single word “cancer” sounds devastating and its announcement transforms the patient’s life, with an upcoming death sensation that could pose a psychological harm to the patient. Just to mention, for the urologist not to over estimate cancer and not to over treat it with interventions that may definitely alter the quality of life of the patient: radical prostatectomy causes urinary incontinence in 5-20% of patients and erectile disfunction in 40-70% of them. ¿ Does cancer localized to the prostate gland really exist? The question arises now between the cases of cancer that are diagnosed while they are not significative and the ones that have already surpassed the capsule.